1992
DOI: 10.1002/apmc.1992.051950113
|View full text |Cite
|
Sign up to set email alerts
|

Die kristallisation eines geschmolzenen molekülkomplexes aus hochmolekularem polyoxyethylen und harnstoff

Abstract: ZUSAMMENFASSUNG:Die Strukturveranderungen eines Molekulkomplexes (MK) aus Polyoxyethylen und Harnstoff beim Abkuhlen aus dem geschmolzenen Zustand werden kalorimetrisch und rentgenographisch untersucht. Es wird festgestellt, dalj eine polymorphe Hochtemperaturform des MK entsteht, die beim Abkuhlen in die bekannte Kristallform des MK mit hexagonaler Kristallmodifikation ubergeht. SUMMARYThe structural transformation of a molecular complex (MC) of polyoxyethylene and urea on cooling from the molten state has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In contrast, the β complex has a 12:8 EO:urea stoichiometry and it is much more difficult to prepare because of its incongruent melting at 90 °C that yields a PEO‐rich liquid and crystals of the α complex 12. It has most often been obtained by melt‐quenching the α complex, but this process leads to a metastable mixture of β complex and urea 4, 5. We recently showed that the pure β complex prepared by electrospinning is thermodynamically stable and suggested an intercalated structure with layers of PEO and urea 16…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the β complex has a 12:8 EO:urea stoichiometry and it is much more difficult to prepare because of its incongruent melting at 90 °C that yields a PEO‐rich liquid and crystals of the α complex 12. It has most often been obtained by melt‐quenching the α complex, but this process leads to a metastable mixture of β complex and urea 4, 5. We recently showed that the pure β complex prepared by electrospinning is thermodynamically stable and suggested an intercalated structure with layers of PEO and urea 16…”
Section: Resultsmentioning
confidence: 99%
“…These complexes sometimes present an incongruent fusion, in which case they typically melt to yield a polymer‐rich peritectic liquid and crystals of the pure small molecule. This creates a challenge for the preparation of pure complex samples when using most common synthesis methods such as cocrystallization from concentrated solutions, melt‐cooling, or solvent casting 2–8. Indeed, the system has to pass through a region of the phase diagram where crystallization of the small molecule is thermodynamically favored and, as a consequence, samples often consist in mixtures of the complex with crystals of the small molecule and residual polymer.…”
Section: Introductionmentioning
confidence: 99%